2022
DOI: 10.5194/egusphere-2022-1093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerating models for multiphase chemical kinetics through machine learning with polynomial chaos expansion and neural networks

Abstract: Abstract. The heterogeneous chemistry of atmospheric aerosols involves multiphase chemical kinetics that can be described by kinetic multi-layer models (KM) explicitly resolving mass transport and chemical reaction. However, KM are computationally too expensive to be used as sub-modules in large-scale atmospheric models, and the computational costs also limit their utility in inverse modelling approaches commonly used to infer aerosol kinetic parameters from laboratory studies. In this study, we show how machi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In the atmosphere, carbonate radical initiated SO 2 oxidation scheme over a real system metric will be more complicated under diverse variable environment conditions (e.g., RH, light intensity, and accumulating growth of CO 2 concentration) and dust constituents, which is a challenging task. Fortunately, machine‐learning (ML) provides a promising approach to accelerate the prediction of atmospheric chemical characteristics and aerosol constituents (Berkemeier et al., 2023; J. Gao et al., 2022; Qin et al., 2022; Song et al., 2021) through efficient data training and analysis. Following this reasoning, we applied this promising method to reduce the large human resource cost coming from the traditional control variate measurement strategy and to reveal the fundamental driver of significance in triggering the fast sulfate production from multitudinous environmental variables and constituents by the established “train” model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the atmosphere, carbonate radical initiated SO 2 oxidation scheme over a real system metric will be more complicated under diverse variable environment conditions (e.g., RH, light intensity, and accumulating growth of CO 2 concentration) and dust constituents, which is a challenging task. Fortunately, machine‐learning (ML) provides a promising approach to accelerate the prediction of atmospheric chemical characteristics and aerosol constituents (Berkemeier et al., 2023; J. Gao et al., 2022; Qin et al., 2022; Song et al., 2021) through efficient data training and analysis. Following this reasoning, we applied this promising method to reduce the large human resource cost coming from the traditional control variate measurement strategy and to reveal the fundamental driver of significance in triggering the fast sulfate production from multitudinous environmental variables and constituents by the established “train” model.…”
Section: Resultsmentioning
confidence: 99%
“…in affecting the SO 2 uptake capability in the presence of CO 2 . Fortunately, the booming machine‐learning (ML) approach has been reported to have great potential to predict atmospheric chemicals characteristic and secondary aerosol constituents (Berkemeier et al., 2023; J. Gao et al., 2022; Qin et al., 2022; Song et al., 2021). Additionally, this economic method can dramatically save the cost of labor source and reduce the uncertainties coming from the conventional control variate measurement, and elucidate the nonlinear relationship between the variable feature and considered outcome, making it possible to reveal the fundamental drivers (environmental conditions or constituents) of significance in determining the SO 2 uptake capability from massive quantities of the complicated lab‐based data set of multitudinous characteristics (T. Wang et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…4 are possible with kinetic multi-layer models, which have become the state-of-the-art in aerosol science. 34,[36][37][38]54 AL-POM only probes birefringent phases, therefore it is specic and could be used for chemical kinetics in a similar way to the use of SAXS as a tool to measure reaction kinetics of specic self- organised structures. 21 Application of a kinetic multi-layer model to those kinetic data could then provide insights into the real-world impact of a particular phenomenon (e.g.…”
Section: Following Water Uptake During Humidicationmentioning
confidence: 99%
“…A SM can be used to substitute the template model in applications that benefit from low computational cost in exchange for slightly increased model uncertainty. Satisfactory model accuracy can be ensured by a sufficient size of the training data set, and therefore depends on the initial investment of computational resources [20]. SM have helped solving the issue of computational cost in many fields of research, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…SM can also aid inverse modelling approaches. Berkemeier et al 2023 [20] showed that SM-supported fit ensemble acquisition greatly outperforms regular sampling with the kinetic multi-layer model of aerosol surface and bulk chemistry (KM-SUB) [5] in terms of acquired fits for a given computational effort. However, it remains unclear how SM uncertainty affects the reliability of inverse modelling techniques.…”
Section: Introductionmentioning
confidence: 99%